Annual report of the committee on gynecologic oncology, the Japan Society of Obstetrics and Gynecology: Annual patients report for 2015 and annual treatment report for 2010. Issue 2 (13th November 2018) - Nagase, Satoru; Ohta, Tsuyoshi; Takahashi, Fumiaki; Enomoto, Takayuki; ,
Abstract: Aim: To provide information including the trend of gynecological malignancies in Japan, we hereby present the Annual Patient Report for 2015 and the Annual Treatment Report for 2010 on the outcomes of patients who started treatment in 2010. Methods: The Japan Society of Obstetrics and Gynecology maintains an annual tumor registry where information on gynecological malignancies from various participating institutions is gathered. The data of patients whose treatment was initiated in 2015 were analyzed retrospectively. Survival of the patients who started treatment in 2010 was analyzed by using the Kaplan–Meier, log‐rank and Wilcoxson tests. Results: Treatment was initiated in 2015 for 7527 patients with cervical cancer, 10 119 with endometrial cancer, 6424 with ovarian cancer and 2181 with ovarian borderline tumors. This clinicopathological information was summarized as the Patient Annual Report. Prognoses were analyzed across 4309 patients with cervical cancer, 5054 with endometrial cancer and 3423 with ovarian cancer, whose treatment was initiated in 2010. The 5‐year survival rates of the patients with cervical cancer were 92.1%, 74.2%, 52.0%, and 29.8% for stages I, II, III, and IV, respectively. The 5‐year survival rates for the patients with endometrial cancer were 94.3%, 88.8%, 74.0% and 26.6% for stages I, II, III and IV, respectively. The 5‐year survival rates for the patients with ovarian cancer (surface epithelial‐stromal tumors) were 88.5%, 80.1%, 46.3% and 36.2% for stages I, II, III and IV, respectively. Conclusion: The annual tumor report is an important survey that provides knowledge on gynecological malignancy trends in Japan.